Blended Learning in M-learning Era: A Leadership Program Case in Pharmaceutical Industry - SU, HANG (2018)
The rapid development of mobile technology and internet brought a new set of challenge and chance to blended learning. To address this issue, this paper aims to extend research about the critical success factors and practical framework for blended learning in the new era through a leadership program case in pharmaceutical industry in China, which was also part of my job before I took this master course. I conduct this research by integrating traditional theoretical constructs associated with new conception and applications brought by the new technology in learning theories such as behavioral and experiential learning theory literatures. The research findings highlight the importance of situated learning, learning process management and the establishment of learning transfer system. At the same time, new technology also brought extra issues to consider. This dissertation concludes with a discussion of the implications of the practical framework for future research and practice.